Fire‐Resistant Structural Material Enabled by an Anisotropic Thermally Conductive Hexagonal Boron Nitride Coating. (21st January 2020) - Gan, Wentao; Chen, Chaoji; Wang, Zhengyang; Pei, Yong; Ping, Weiwei; Xiao, Shaoliang; Dai, Jiaqi; Yao, Yonggang; He, Shuaiming; Zhao, Beihan; Das, Siddhartha; Yang, Bao; et al.
Abstract: Fire retardant coatings have been proven effective at reducing the heat release rate (HRR) of structural materials during burning; yet effective methods for increasing the ignition temperature and delay time prior to burning are rarely reported. Herein, a strong, fire‐resistant wood structural material is developed by combining a densification treatment with an anisotropic thermally conductive flame‐retardant coating of hexagonal boron nitride (h‐BN) nanosheets to produce BN‐densified wood. The thermal management properties created by the BN coating provide fast, in‐plane thermal diffusion, slowing the conduction of heat through the densified wood, which improves the material's ignition properties. Compared with densified wood without the BN coating, a 41 °C enhancement in ignition temperature ( T ig ), a twofold increase in ignition delay time ( t ig ), and a 25% decrease in the maximum HRR of BN‐densified wood can be achieved. As a proof of concept for scalability, the pieces of the BN‐densified wood are fabricated with a length larger than 25 cm, width greater than 15 cm, and thickness more than 7 mm. The improved thermal management, fire resistance, mechanical strength, and scalable production of BN‐densified wood position it as a promising structural material for safe and energy‐efficient buildings. Abstract : An anisotropic thermally conductive hexagonal boron nitride (h‐BN) coating strategy is demonstrated to increase the ignition temperature and delay time prior to burning for densified wood. The BN‐densified wood demonstrates enhanced fire resistance, outstanding mechanical properties, and scalable production, holding great potential for safe and energy‐efficient construction applications.